Studies in Middle Assyrian Chronology and Religion - Fine, H. A.
Introduction - 1. The 15th Century - 2. The 14th Century (General Chronology, the Career of Bêl-qarrâd, the Family of Nûr-Kubi, iddin-Kubi and his Son) - 3. The 13th Century (General Chronology, Zêr-iqîša mâr Iakkija, the Family of Aššur-aḫ-iddina, Activity of Bâbu-aḫ-iddina).